The effects of X-ray background on the X-ray emission from the Galactic supernova remnants - Cesur, Nergis; Sezer, Aytap; Hudaverdi, Murat (Tubitak Scientific & Technological Research Council Turkey, 2018)
We present the results of an X-ray background emission study of the well-known Galactic supernova remnants (SNRs) Gas A, RCW 86, RX J1713.7 - 3946, and SN 1006 by using the archival Chandra and XMM-Newton X-ray Observatories data. With the advent of detector technologies and increased capability of the spectral resolutions, accurate background modelling for the extended sources, such as SNRs, is getting crucial at the modelling step since it might be effective on estimating the physical parameters of the plasma. For this purpose, we concentrate on the background emission spectral modelling by investigating its spectral parameters and components. Hence, the results of the modelled background spectra of these four SNRs are presented by using the combination of thermal and nonthermal emission models properly to the background components.
Keywords: X-rays; interstellar medium; supernova remnants; X-ray background; SPECTRA; Physics